The environmental impacts of one of the largest tailing dam failures worldwide - Hatje, Vanessa; Pedreira, Rodrigo M. A.; Rezende, Carlos Eduardo de; Franca Schettini, Carlos Augusto; Souza, Gabriel Cotrim de; Marin, Danieli Canaver [UNESP]; Hackspacher, Peter Christian [UNESP] (Nature Publishing Group, 2017)
The impacts of the SAMARCO iron tailing spill along more than 650 km, between the dam and the plume of the Doce River in the Atlantic, were assessed by the determination of toxic metals. The tailing spill caused a substantial increase in suspended sediment loads (up to 33,000 mg L-1), in addition to large depositions of waste along the Doce basin. The highest estimated transport of dissolved metals was observed for Fe (58.8 mu g s(-1)), Ba (37.9 mu g s(-1)) and Al (25.0 mu g s(-1)). Sediments reached the highest enrichment factors (EFs) for Hg (4,234), Co (133), Fe (43), and Ni (16), whereas As (55), Ba (64), Cr (16), Cu (17), Mn (41), Pb (38) and Zn (82) highest EFs were observed for suspended particulate matter (SPM). Iron, As, Hg, Mn exceeded sediment quality guidelines. Therefore, the risk of occurrence of adverse effects is highly possible, not only due to the dam failure, but also due to the Fe mining and the artisan Au mining. Heavy rain episodes will likely cause enhanced erosion, remobilization, and transport of contaminated particles, sustaining high inputs of SPM and metals for the years to come and threatening the ecosystem services.